The discursive representations of borderlands: an analysis of visual culture and conceptions of place occurring at the U.S.-Mexico border - Kofoed, Emily Sue (Kansas State University, 2009)
Geographical borders represent a clash of cultures. Those inhabiting or moving through borderlands struggle to maintain a sense of place and, in turn, an understanding of cultural collective memory. This project strives to understand how the visual and discursive elements that constitute the U.S.-Mexico border function rhetorically to communicate difference and establish place. By utilizing a social semiotics perspective, I analyzed visual rhetoric of the U.S.-Mexico border in the form of photographs and maps produced in both the United States and Mexico. Additionally, a theory of cultural memory was used to explore the confluence of events and rhetorical phenomena that shape the U.S.-Mexico border, and allow the U.S.-Mexico border to shape the rhetoric of the countries it divides. I argued that borders are inherently rhetorical and the intersection of visual elements, culture, place and memory make borders important to understand from an anthropological, and geographical perspective, as well as a rhetorical one. This project holds political and social implications for the relationship between the United States and Mexico, and reveals key findings regarding how cultural identity is negotiated in fragmented places like borderlands.
Keywords: Speech communication; Rhetoric; Speech Communication (0459)